Digital Reconstruction of the Snake King Festival Intangible Cultural Heritage in Zhanghu Town：A Multidimensional AI-enabled Animation Approach - Liang, Bingbing; Sriruksa , Kittisan; Wongpongkham , Niyom; Sriruksa , Arunee (Journal of Ecohumanism, 2024)
The international community has widely recognized the importance of preserving Intangible Cultural Heritage (ICH) for sustainable development. However, due to its inherent intangibility, ICH is at risk of degradation and disappearance. Although public participation is crucial to ICH preservation, it remains insufficient in many systems. Against this backdrop, this paper explores and emphasizes the necessity of public involvement in ICH preservation and proposes an innovative AI-based animation generation workflow to enhance the digital preservation and dissemination of ICH. Integrated into a 12-minute animation, this workflow vividly recreates the core elements of the Snake King Festival in Zhanghu Town, Fujian Province. Based on an extensive survey of the Snake King Festival dataset, this study successfully employs this AI animation generation technology to digitally reconstruct the dynamic elements of ICH, significantly outperforming traditional methods. The strategies proposed not only accelerate the digital preservation of intangible cultural heritage but also provide a technical blueprint for similar projects, offering broad potential for widespread adoption. The ultimate goal is to enhance public understanding and participation in ICH by demonstrating the immense potential of this AI animation technology workflow in the digital preservation of ICH, contributing to the sustainability of global ICH. Despite significant progress, further enhancements in the cultural accuracy and fidelity of the generated content are needed. Future research will focus on optimizing the model to capture cultural characteristics more precisely and explore the application of this method in protecting more types of ICH.